2018
DOI: 10.1016/j.scitotenv.2018.04.070
|View full text |Cite
|
Sign up to set email alerts
|

Physical legacy of freshwater bivalves: Effects of habitat complexity on the taxonomical and functional diversity of invertebrates

Abstract: Bivalves may play a major role in structuring aquatic communities. This may be especially relevant in aquatic communities dominated by non-native invasive bivalves, which can contribute to the increase of habitat homogenization. In this study, we assess how habitat homogenization, through the reduction of empty bivalve shells identities, influences the macroinvertebrate assemblages. Towards this end, a manipulative experiment with the empty shells of two native (Potomida littoralis and Unio delphinus) and one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 47 publications
2
20
0
Order By: Relevance
“…Shells can have many positive influences from an ecological perspective. They provide suitable substrate for attachment and refuge for many species, reduction of the physical and/or physiological stress, and also as reservoirs of nutrients to the benthic compartment (Gutiérrez et al, 2003;Ilarri et al, 2012Ilarri et al, , 2015bIlarri et al, , 2018Wenger et al, 2019). In fact, in previous studies performed in the Minho River it was possible to observe that the shells of the selected species attracted a relevant and similar macrozoobenthic community (Ilarri et al, 2015b).…”
Section: Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Shells can have many positive influences from an ecological perspective. They provide suitable substrate for attachment and refuge for many species, reduction of the physical and/or physiological stress, and also as reservoirs of nutrients to the benthic compartment (Gutiérrez et al, 2003;Ilarri et al, 2012Ilarri et al, , 2015bIlarri et al, , 2018Wenger et al, 2019). In fact, in previous studies performed in the Minho River it was possible to observe that the shells of the selected species attracted a relevant and similar macrozoobenthic community (Ilarri et al, 2015b).…”
Section: Speciesmentioning
confidence: 99%
“…However, the water flow differs between sites, with L1 located in the main canal of the Minho River and being characterized by a fastflowing (lotic) water regime during the entire year with the exception of summer and early autumn and L2 located in a side arm of the Minho River and being characterized by a slow-flowing (lentic) water regime throughout the entire year. The classification of sites according to the water flow conditions was done qualitatively, based on previous studies performed in the study area (Sousa et al, 2007(Sousa et al, , 2008Ilarri et al, 2015aIlarri et al, , 2015bIlarri et al, , 2018Novais et al, 2017) and on empirical evidence of the water regime throughout the study period (authors personal observations).…”
Section: Study Areamentioning
confidence: 99%
“…While bivalve soft tissue decomposes quickly, shells persist for many decades (5-30 years), providing habitat for other stream biota (Strayer and Malcom, 2007;Ilarri et al, 2015;Atkinson et al, 2018). Over time, the benthos will be more homogenous as old shells dissolve and new relic shells are produced by a less diverse mussel assemblage ultimately altering benthic microhabitat characteristics and macroinvertebrate community structure ( Figure 1E; Ilarri et al, 2018).…”
Section: Changes In Habitat Provided By Shellsmentioning
confidence: 99%
“…Other studies have shown that shell density of C. fluminea is positively associated with biomass, diversity, and density of macroinvertebrates (Ilarri et al, 2012). Shells resulting from die-offs can also have significant effects on estuarine and freshwater macroinvertebrates than can use them as substrate or as refuge from predators (e.g., Ilarri et al, 2012Ilarri et al, , 2014Ilarri et al, , 2018Bódis et al, 2014b;Novais et al, 2015).…”
Section: Habitat Creationmentioning
confidence: 99%